Teachers’ Roles in Developing Third-Grade Students’ Reading Habits Through a Deep Learning Approach - Imas Ratna Wulan; Aang Solahudin Anwar; Anggy Giri Prawiyogi; Depi Prihamdani (MASI Mandiri Edukasi, 2026)
This study aimed to analyze the role of teachers in fostering reading habits among third-grade elementary school students through the implementation of a deep learning approach. The research was conducted at SDN Tegalsawah II, Karawang Timur, Indonesia, over one academic semester using a descriptive qualitative design. The participants consisted of classroom teacher informants selected through purposive sampling based on their involvement in literacy instruction and at least two years of teaching experience, while third-grade students served as supporting participants through classroom observations. Data were collected through semi-structured interviews, classroom observations, and documentation, and analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing/verification. The findings indicate that teachers play important roles as facilitators, motivators, and learning guides in creating a literacy-supportive classroom environment. Their strategies include establishing daily reading routines before lessons, providing engaging reading materials, utilizing classroom reading corners, and motivating students through encouragement and positive reinforcement. Classroom observations and teacher interviews suggest that implementing the deep learning approach was associated with students demonstrating deeper engagement in reading activities, including efforts to interpret texts, participate in discussions, and relate reading content to everyday experiences. Nevertheless, students' reading habits varied, with some showing independent reading behaviors while others continued to require teacher guidance and motivation. Supporting factors included strong teacher commitment and the availability of reading resources, whereas limited student interest in reading and an insufficient book collection remained major challenges. Overall, the findings suggest that consistent teacher involvement, appropriate literacy strategies, and the sustained implementation of deep learning principles contribute to the development of reading habits in elementary school students. However, further studies involving broader participant groups are needed to strengthen these findings.